SYNTHESIS OF SOME NOVEL POLYURETHANES AND THEIR SCOPE OF APPLICATION IN DIFFERENT FIELDS (International Journal of Food and Nutritional Sciences, 2022)
Basically polyurethanes are synthesized by reacting a diisocyanate, polyol and a chain extender diol. Once the chemical reaction of its components has taken place, the result is a polyurethane foam that is completely inert and harmless to humans. Cementitious polyurethane flooring is one of the most popular surface choices for clients working within the food and beverage sector as it offers higher strength, better heat resistance and improved chemical resistance than epoxy or MMA alternatives. Thus our choice is to synthesize some polyurethanes and its block copolymers. So, a series of polyurethane based on 4,4'-diphenylmethane diisocyanate (MDI), polypropylene glycol (PPG, M.W. 1000), 1,4-butane diol (BD) and 1,1,2,2-tetraphenylethanediol (TPED) were synthesized by the prepolymer method. The molar ratio maintained in all the synthesis was MDI:PPG:short chain diol( 3:1:2). Here, MDI and PPG were reacted first thermally followed by chain extension with short-chain diols BD and TPED. Polyurethanes having such sterically hindered carbon-carbon bonds may also act as thermal macroiniferters. These thermal polyurethane macroiniferters were used to prepare polyurethane-block polyvinyl copolymers. A photoinitiator, N,N-Diethyldithiocarbamato-(1,2)-propanediol (DCPD) with a pendent N,N-Diethyldithiocarbamato group was synthesized from sodium N,N-Diethyldithiocarbamate (NaSR) and 3-chloro-1,2-propanediol(CPD). Polyurethane macrophoto iniferters having such pendent N, N-diethyl dithiocarbamato groups in its backbone were used to synthesize polyurethane-graft-poly 2-Hydroxyethyl methacrylate copolymers through photopolymerization. The photopolymerization reactions were carried out in the Heber multilamp photochemical reactor (Compact- LP-MP 88) at 254 nm. The thermal properties of both the polyurethanes and their corresponding vinyl block and graft copolymers were studied by thermogravimetric analysis (TGA).